2013
DOI: 10.1186/1471-2458-13-247
|View full text |Cite
|
Sign up to set email alerts
|

Heavy episodic drinking and soccer practice among high school students in Brazil: the contextual aspects of this relationship

Abstract: BackgroundHeavy episodic drinking (HED) (consumption of five or more drinks on the same occasion) among adolescents is related to several problems and partaking in sport or physical activities has been suggested as an option to prevent or reduce alcohol consumption among this population. The aim of this study was to investigate the relationship between soccer practice and heavy episodic drinking among high school students from Brazil.MethodsData were obtained from a cross-sectional study among a representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
2
28
0
6
Order By: Relevance
“…This study also reported a significant difference between the proportions of players that reported getting in a fight because of their drinking (32%) compared with the national sample (15%) [3]. Similar patterns have been found in studies in New Zealand [4] and Brazil [5]. A cross‐sectional US study also found spectators drank a significantly more drinks on game days (mean: 5.6 drinks) compared with other social occasions (mean: 4.86 drinks) [6].…”
Section: Introductionsupporting
confidence: 85%
“…This study also reported a significant difference between the proportions of players that reported getting in a fight because of their drinking (32%) compared with the national sample (15%) [3]. Similar patterns have been found in studies in New Zealand [4] and Brazil [5]. A cross‐sectional US study also found spectators drank a significantly more drinks on game days (mean: 5.6 drinks) compared with other social occasions (mean: 4.86 drinks) [6].…”
Section: Introductionsupporting
confidence: 85%
“…3,8,14 Some authors point out the importance of social and cultural aspects [14][15][16] in understanding the relationship between sports and drugs. Adolescents are subject to considerable peer influence regarding alcohol and tobacco use.…”
mentioning
confidence: 99%
“…In first place, worldwide research demonstrated the increasingly pervasive nature of professional sports-related alcohol marketing [2]. Secondly, alcoholic beverages are commonly associated with sports [6], as for many spectators beer is a fixed component of a soccer event.…”
Section: Discussionmentioning
confidence: 99%